1993
DOI: 10.2307/1369365
|View full text |Cite
|
Sign up to set email alerts
|

Variability Profiles for Line Transect Bird Censuses in a Tropical Dry Forest in Mexico

Abstract: Seasonal and temporal patterns of species diversity and abundance in the avifauna of Chamela, Jalisco, Mexico, were studied in different habitats in the coastal tropical dry forest. Species richness did not differ among three different transects. The number of species was temporally homogeneous. Species diversity was similar for all three transects, but it changed to higher values during the rainy season at arroyo habitats and during the dry season (winter) at disturbed habitats. Population fluctuations observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
9

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
2
17
0
9
Order By: Relevance
“…Seasonal variation of the avifauna in the present study was similar to that found in other tropical forest regions (Chamela region in Jalisco, Mexico and Maringá in Paraná, Brazil; Ornelas et al, 1993, Krügel & Anjos, 2000 where the species richness was greater from October to November. Our results show that species composition did not differ significantly across the 24 study sites, and similarities of different levels among the sites were common.…”
Section: Discussionsupporting
confidence: 89%
“…Seasonal variation of the avifauna in the present study was similar to that found in other tropical forest regions (Chamela region in Jalisco, Mexico and Maringá in Paraná, Brazil; Ornelas et al, 1993, Krügel & Anjos, 2000 where the species richness was greater from October to November. Our results show that species composition did not differ significantly across the 24 study sites, and similarities of different levels among the sites were common.…”
Section: Discussionsupporting
confidence: 89%
“…If birds select nest sites that provide concealment to decrease the risk of predation, is nest‐site selection based on conditions at the time of nest building or those that will prevail later in the breeding process? For most passerines at our Chamela study site, incubation occurs during the dry season (Ornelas et al 1993). Therefore, even if birds are using cues to select sites that will become more concealed during the rainy season, nest building, egg laying, and incubation take place during the dry season when the foliage provides less concealment.…”
Section: Discussionmentioning
confidence: 99%
“…In the Pacific lowlands of western Mexico, most passerines associated with dry forest select nest sites, build nests, and start incubation at the end of the dry season when the forest is almost completely leafless (Arizmendi et al 1990, Ornelas et al 1993). Chicks hatch when the rains start (Vega Rivera, pers.…”
mentioning
confidence: 99%
“…Bersier & Meyer 1994, Pearman 1997, Tilman et al 1997, Kaspari et al 2000. En el caso especifico de la región de Chamela, trabajos previos han encontrado resultados similares al presente estudio, detectándose una mayor riqueza y abundancia de mamíferos en la VA que en el BTC, en especial durante la época de secas (Ceballos 1989, Mandujano & Gallina 1996, Mandujano 1999, Nuñez & Miller 2000, Valenzuela & Ceballos 2000: sin embargo, no fue el caso de las avifauna, probablemente debido a la gran movilidad de las especies, cambios estacionales en la composición de las especies por migración, y debido a su conducta reproductiva (Ornelas et al 1993). Así mismo, en otros ambientes áridos y estacionales, tales como los desiertos, durante la época de secas, la distribución de las especies de reptiles y anfibios se concentra en los arroyos o ecosistemas con menor estacionalidad ambiental, mayor disponibilidad de recursos y mayor complejidad estructural (Baker 1990, McComb et al 1993aDegenhardt et al 1996, Gómez & Anthony 1996.…”
Section: Secas Lluvias Ambasunclassified